Pharmacology complex compound of pro-gly-pro-leu with heparin: hypoglycemic, fibrinolitic and anticoagulant effects in rats with hyperglycemia - T. Yu. Obergan; N. F. Myasoedov; M. E. Grigorjeva; L. A. Lyapina; T. A. Shubina; L. A. Andreeva (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2019)
Previously it was shown that the use of regulatory peptides of the glyprolin family helps to normalize the hemostasis system and blood glucose levels in experimental resistant hyperglycemia in rats, similar to type 2 diabetes mellitus in humans. It is also known that the anticoagulant heparin inhibits blood coagulation and exhibits a hypoglycemic effect in the body.The aim of the study is to obtain a complex of the Pro-Gly-Pro-Leu (PGPL) peptide and the unfractionated heparin, to study its effect on glucose and anticoagulant fibrinolytic properties and show its ability to restore the impaired functions of the insular and coagulating blood systems in experimental hyperglycemia in rats.Materials and Methods. Laboratory Wistar male rats, intact and with experimentally induced hyperglycemia, were used in the experiment. A complex compound of PGPL and heparin was created with a component ratio of 1:1 (mol/mol), which was administered intranasally to hyperglycemic rats once a day for 5 days at the dose of 1 mg/kg. Similarly, the constituent parts of the complex were administrated in equivalent amounts. The anticoagulant activity was determined by the test of activated partial thromboplastin time, fibrinolysis parameters - by tests of total, enzymatic and non-enzymatic fibrinolytic activities, as well as the activity of a tissue plasminogen activator. In addition, blood glucose was measured using special test strips. Results. The use of the PGPL-heparin complex in the animals with hyperglycemia led to normalization of blood glucose levels, an increase in the anticoagulant and fibrinolytic background of blood plasma. These effects persisted for 6 days after the cancellation of the peptide-heparin complex administration to rat.Conclusion. In the development of experimental hyperglycemia, the PGPL complex with heparin exhibits a combined hypo-glycemic, anticoagulant and fibrinolytic enzymatic and non-enzymatic nature of the effect. In the future, the studied peptide-heparin complex can be used for the prevention and treatment of type 2 diabetes mellitus, complicated by increased blood coagulation.